Teaching Practicum in Pre-Service Teacher Education - Dwiyani Pratiwi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This paper presents a review of the research literature on practicum. Since there have been changes in trends in Teaching Education since the 1960s that also influenced the shift of research topics on practicum, this paper first gives a short review of the research trends in general TE, changing from the teaching process- product paradigm to the investigation of teachers’ mental lives or cognition. Then the actual review will focus on the studies related to the teachers’ beliefs, perspectives, perceptions, understanding, and reasoning, and follows under these topics: student teachers learning, cooperating teachers, and school-university cooperation in the practicum. At the end of this paper, some future studies on teaching practicum are suggested.